2018
DOI: 10.1177/0892705718799832
|View full text |Cite
|
Sign up to set email alerts
|

Development and mechanical characterization of microwave-cured thermoplastic based natural fibre reinforced composites

Abstract: In the present work, polypropylene (PP)- and polyethylene (PE)-based composites were cured using microwave energy with 15% weight percentage of jute and kenaf fibres. The detailed mechanism of microwave curing of the composites has been discussed with suitable illustrations. The mechanical characterization of the microwave-cured composites was carried out using various tests. The scanning electron microscope (SEM) fractographs were used to study the mechanisms of failure. The ultimate tensile strength of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Before the fabrication process, the kenaf fiber mat underwent treatment with a 10 wt% alkaline solution to remove the wax particles and enhance the surface roughness. 8 The fiber mats used in the experiment were of the plain weave pattern. The average diameter of the fiber and the strand was 0.5 mm and 0.02 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the fabrication process, the kenaf fiber mat underwent treatment with a 10 wt% alkaline solution to remove the wax particles and enhance the surface roughness. 8 The fiber mats used in the experiment were of the plain weave pattern. The average diameter of the fiber and the strand was 0.5 mm and 0.02 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Use of microwave energy to process a wide range of materials for various applications has been reported by several authors. [7][8][9][10][11][12][13][14][15][16][17][18][19] The study reported that microwave-assisted heating of nonmetals (polymers) involves the phenomenon of dipolar and conduction loss associated with electric field effect.…”
Section: Introductionmentioning
confidence: 99%
“…33 This can be attributed to the improved heating rate as microwave is a faster and volumetric heating route. 16 The flexural modulus of the foam specimen was calculated using the following equation 34 where F is the flexural load, L is the span length of the specimen, d is the displacement, b is the width of the specimen and h is the height of the specimen.…”
Section: Resultsmentioning
confidence: 99%
“…33 This can be attributed to the improved heating rate as microwave is a faster and volumetric heating route. 16 The flexural modulus of the foam specimen was calculated using the following equation 34 Flexural Modulus ðFMÞ ¼…”
Section: Flexural Behaviourmentioning
confidence: 99%
See 1 more Smart Citation